Studi Komparasi Metode Penyelesaian Mukhtalif Al-Hadīs antara Muhaddisin dan Fuqaha - Muhammad Daud, Zakiul Fuady; Irwanto, Irwanto (Islamika Inside: Jurnal Keislaman dan Humaniora, 2021)
Abstract: Outwardly, there are hadith that seem contradictory between one hadith and another. It happened not because of the inconsistency of the Prophet Muhammad in giving his words but because of the method of hadith researchers in understanding them. In resolving these contradictory hadiths, there are several methods used by scholars. This paper aims to determine the methods used by hadith scholars and fiqh scholars in completing these hadiths and to compare the methods they use. This research is a literature review using content analysis as a data analysis technique. The results of this study indicate that hadith and fiqh scholars have the same sequence of methods in resolving contradictory hadith, they are al-jam'u (compromising), nasakh (abrogating), tarjih (confirming), and tawaqquf methods (moratorium). Only does Imam Abu Hanifah has a different order, they are nasakh, tarjih, al-jam'u, and tawaqquf. The comparison of the methods used by the two groups of scholars, both hadith and fiqh scholars agreed to prioritize the al-jam'u method as an attempt not to paralyze one hadith with other hadiths. However, in contrast to Imam Abu Hanifah, who prioritized the nasakh method rather than the al-jam'u method, consequently there were hadiths that were not used.